2006
DOI: 10.1007/s10803-006-0202-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Working Memory Deficits in Autism

Abstract: Previous studies have reported working memory deficits in autism, but this finding has been inconsistent. One possibility is that deficits in this domain may be present only when working memory load exceeds some limited capacity. High-functioning individuals with autism performed the CANTAB computerized test of spatial working memory. Individuals with autism made more errors than a matched group of typically developing controls on this task, and were less likely to consistently use a specific organized search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
135
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(160 citation statements)
references
References 40 publications
18
135
1
6
Order By: Relevance
“…This is of particular importance when assessing whether cognitive training is appropriate for individuals with ID, as processes such as WM are already severely compromised and may prevent children from engaging with the program at all. Indeed children with Autism have been shown to have impairments in WM (Steele, Minshew, Luna, & Sweeney, 2007) as well as those with WS , (Menghini, Addona, Costanzo, & Vicari, 2010;Rhodes, Riby, Fraser & Campbell, 2011), FXS (Munir, Cornish, & Wilding, 2000;Schapiro et al, 1995) and DS (Lanfranchi, Cornoldi, & Vianello, 2004).…”
Section: Attention Training Vs Working Memory Training In Intellectuamentioning
confidence: 99%
“…This is of particular importance when assessing whether cognitive training is appropriate for individuals with ID, as processes such as WM are already severely compromised and may prevent children from engaging with the program at all. Indeed children with Autism have been shown to have impairments in WM (Steele, Minshew, Luna, & Sweeney, 2007) as well as those with WS , (Menghini, Addona, Costanzo, & Vicari, 2010;Rhodes, Riby, Fraser & Campbell, 2011), FXS (Munir, Cornish, & Wilding, 2000;Schapiro et al, 1995) and DS (Lanfranchi, Cornoldi, & Vianello, 2004).…”
Section: Attention Training Vs Working Memory Training In Intellectuamentioning
confidence: 99%
“…DA exposure and ASD also share commonality in the expression of repetitive behaviors [51,52] and heightened seizure activity, which occurs in approximately one quarter of autistic children [53][54][55]. Less obvious behavioral phenotypes that are shared by exposure to toxic levels of DA and ASD include deficits with spatial memory, which are expressed by both DA-exposed California sea lions and children with ASD [56,57].…”
Section: Toxicity Of Domoic Acidmentioning
confidence: 99%
“…Studies have used different tools in the same sample of participants with conflicting results. Studies have also been divided into three categories based on their findings: studies that found a deficit in STM/WM in children with ASD (Nydén et al, 1999;Minshew & Goldstein, 2001;Goldberg et al, 2005;Verte et al, 2006;Steele, Minshew, Luna, & Sweeney, 2007;Corbett et al, 2009); studies that failed to detect any deficit (Rumsey & Hamburger, 1988;Ozonoff & Strayer, 2001;Edgin & Pennington, 2005;Happé et al, 2006;Chan et al, 2009), and those studies with mixed results (Prior & Hoffmann, 1990;Rumsey & Hamburger, 1990;Bennetto et al, 1996;Minshew et al, 1992;Williams, Goldstein, Carpenter, & Minshew, 2005;Alloway, Rajendran, & Archibald, 2009;Zinke et al, 2010) owing to an uneven performance across the trials. This has led some researchers to support the view that individuals with ASD present no deficits in memory and merely fail to use the appropriate storage strategies (Minshew et al, 1992;Bennetto et al, 1996).…”
Section: Memorymentioning
confidence: 99%